2021
DOI: 10.11648/j.ajp.20210701.12
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Child COVID-19 Patients of Bangladesh

Abstract: Background: Millions of people worldwide have been affected by the COVID-19 pandemic. Due to the prevalence of malnutrition, refusal of immunization during a pandemic, nutritional anemia, air pollution, poverty, poor parental education, inadequate access to high-quality acute healthcare, the clinical characteristics and outcomes of children in Bangladesh may vary from other countries. Information on clinical presentations, outcomes, the relationship between disease incidence and the prevalence of associated di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Initial reports during the pandemic suggested children have milder illness during acute infection [17] . [18][19][20][21] Male female ratio in our study was 1:1 but in other study it was 1.2:1. [18][19][20][21] .…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Initial reports during the pandemic suggested children have milder illness during acute infection [17] . [18][19][20][21] Male female ratio in our study was 1:1 but in other study it was 1.2:1. [18][19][20][21] .…”
Section: Discussionmentioning
confidence: 52%
“…[18][19][20][21] Male female ratio in our study was 1:1 but in other study it was 1.2:1. [18][19][20][21] . The mean duration of hospitalization was 6.79±7.06 days.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This rate is higher than that found by Ghosh et al (1.4%) and Anwar et al (4.1%). 26,32 The low number of neonates among their studies might explain the difference. However, Trevisanuto et al found zero case fatalities among 44 newborns with COVID-19.…”
Section: Discussionmentioning
confidence: 95%
“…Nearly half of the participants were aged less than one year, which is higher than that found by Anwar et al he median age of pediatric patients with COVID-19 varies from study to study based on the target population and method of selection. 26 A systematic review on the pediatric group by Patel found that the reported median age ranges from 1 to 11 years. The author also presents a composite mean age of 7.9 years with an age range between 1 day and 17 years, similar to our study.…”
Section: Discussionmentioning
confidence: 99%